Balancing Work and Caregiving: Tips for Employees - Carolyn S. Wilken (EDIS)
FCS-2260, a 3-page fact sheet by Carolyn Wilken, is the fourth in a series on caregiving and aging. Balancing employment and caregiving can be very difficult. This publication will help employees work with their employers, their families, and their care receivers to make sure that everyone is getting what they need. Contains information on FMLA and a list of helpful resources. Published by the UF Department of Family, Youth and Community Sciences, November 2006.